2018
DOI: 10.1016/j.clnesp.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Should omega-3 fatty acids be used for adjuvant treatment of cancer cachexia?

Abstract: Future cachexia trials would likely benefit from studying a single tumour type with earlier stage disease, with probably different dosage depending on the cancer type and its inflammatory profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 22 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…Intervention studies showed that EPA may attenuate deterioration of nutritional status and may aid in improving calorie and protein intake. Recent systematic reviews found that EPA can reduce inflammation and has a potential to modulate the nutritional status/body composition [66,67]. Furthermore, some studies suggest that n−3 fatty acids inhibit proliferation of cancer cells [68] and might decrease CT toxicity [69].…”
Section: Resultsmentioning
confidence: 99%
“…Intervention studies showed that EPA may attenuate deterioration of nutritional status and may aid in improving calorie and protein intake. Recent systematic reviews found that EPA can reduce inflammation and has a potential to modulate the nutritional status/body composition [66,67]. Furthermore, some studies suggest that n−3 fatty acids inhibit proliferation of cancer cells [68] and might decrease CT toxicity [69].…”
Section: Resultsmentioning
confidence: 99%
“…The use of omega-3 PUFA supplementation to treat anorexia-cachexia syndrome is commonly employed in cancer patients. However, the beneficial effects of these molecules for this complication are still questionable [101]. Particularly, there are no treatment plans for anorexia-cachexia syndrome in virtue of the multifactorial characteristics of this syndrome [102], demonstrating that an open discussion on the benefits of low-cost management, such as fish oil supplementation, is extremely important for clinical practice.…”
Section: Anorexia-cachexia Syndromementioning
confidence: 99%
“…However, the experimental evidence supporting the use of omega-3 fatty acids in the treatment of cancer cachexia is far from conclusive. A recent systematic review of studies published from 2000 to 2015 examining the impact of omega-3 fatty acids on cancer cachexia identified that out of 140 studies only 7 reached the quality threshold of inclusion according to the Delphi list (68). Out of those 7 studies, only one study in pre-cachexic cancer patients demonstrated a statistically positive effect of omega-3 fatty acids (69, 70).…”
Section: Counteracting Skeletal Muscle Loss With Omega-3 Fatty Acidsmentioning
confidence: 99%
“…Out of those 7 studies, only one study in pre-cachexic cancer patients demonstrated a statistically positive effect of omega-3 fatty acids (69, 70). The fact that only 5% of available studies reached the required threshold of quality in this systematic review (68), highlights the challenges faced by scientists and clinicians in conducting high-quality, statistically-powered, randomized controlled trials in this specialized population.…”
Section: Counteracting Skeletal Muscle Loss With Omega-3 Fatty Acidsmentioning
confidence: 99%